Barbara Thiering’s interpretation of Jesus’ life - Naudé, JA (Acta Theologica, 2022)
The purpose of this paper is to present arguments to disprove Thiering’s claim that documents like the New Testament, Dead Sea Scrolls, the writings of Josephus, etc. might reveal the actual historical Jesus. Her use of the pesher technique is also discussed critically. It is shown that Thiering’s pesher technique is a misconception of the pesher used in the Qumran commentaries and that she overestimated the importance of pesher as a method of text interpretation. The evaluation of Thiering’s attempt to equate Christianity and Essenism, as well as the so-called similarities between the Qumran community and early Christianity, will follow logically.